ANALYSIS OF THE INFLUENCE OF PARENTS AND CHURCHES ON YOUTH PARTICIPATION IN WORSHIP: A QUANTITATIVE STUDY AT ANUGRAH BIBLE CHURCH IN BOLAANG MONGONDOW - Risa Yulianti; Degunias Ton; Padricx Aner Madai Manu; Sandro Semuel Lami (Universitas HKBP Nommensen, 2026)
Youth participation in worship is an important indicator of the sustainability of church faith formation. However, the literature only identifies the family and the church as factors influencing the spiritual lives of young people. However, few studies simultaneously analyze the relative contributions of these two factors in explaining youth worship activities in the context of local churches in Indonesia. This study aims to analyze the influence of the roles of parents and the church on youth worship activities, both partially and simultaneously. The study used a quantitative approach with a correlational design. The sample consisted of 30 youth aged 16-30 years from two congregations of the Anugerah Bible Church in Bolaang Mongondow, selected using a purposive sampling technique. Data were collected through a structured questionnaire that measured the role of parents, the role of the church, and youth worship activities. Data were analyzed using Pearson correlation tests, as well as simple linear regression and multiple linear regression to examine the magnitude of the influence and contribution of each variable. The results of the study indicate that the role of parents has a significant influence on youth worship activities with an effective contribution of 50.9% and a relative contribution of 83.8%. While the role of the church does not show a significant influence with an effective contribution of 9.8% and a relative contribution of 16.2%. Simultaneously, the roles of parents and the church explain 60.7% of the variation in youth worship activities. Thus, Christian development and education place the family as the primary agent in shaping the spiritual life of young Christians, while the church plays a supporting role that complements the process. Therefore, the church needs to develop a development strategy that strengthens partnerships with parents so that the spiritual formation and worship participation of young people can take place more effectively.Keywords: Literacy Mentoring, Numeracy Mentoring, Education Quality, Elementary Teachers, Professional Development